INDIRECT SEARCHES FOR NEW PHYSICS - Petrov, Alexey A., 1971- (BOCA RATON : CRC PRESS, 2021)
This is the first book to discuss the search for new physics in charged leptons, neutrons, and quarks in one coherent volume. The area of indirect searches for new physics is highly topical; though no new physics particles have yet been observed directly at the Large Hadron Collider at CERN, the methods described in this book will provide researchers with the necessary tools to keep searching for new physics.It describes the lines of research that attempt to identify quantum effects of new physics particles in low-energy experiments, in addition to detailing the mathematical basis and theoretical and phenomenological methods involved in the searches, whilst making a clear distinction between model-dependent and model-independent methods employed to make predictions. This book will be a valuable guide for graduate students and early-career researchers in particle and high energy physics who wish to learn about the techniques used in modern predictions of new physics effects at low energies, whilst also serving as a reference for researchers at other levels. Key features:Takes an accessible, pedagogical approach suitable for graduate students and those seeking an overview of this new and fast-growing fieldIllustrates common theoretical trends seen in different subfields of particle physicsValuable both for researchers in the phenomenology of elementary particles and for experimentalists
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Nuclear Physics; SCIENCE / Physics; SCIENCE / Quantum Theory; Particles (Nuclear physics)